Determination Of Paracetamol, Guaiphenesin, Chlorpheniramine Maleate And Phenylpropanolamine Hydrochloride In Cough And Cold Tablet Using High Performance Liquid Chromatography - Ardiyanti, Yani Abdul (Journal of Food and Pharmaceutical Sciences, 2014)
The method of choice for analysis of drugs in multi-component preparations is chromatographic based technique such as high performance liquid chromatography (HPLC). A liquid chromatographic method was applied for the analysis paracetamol (PCT), guaiphenesin (GG), chlorpheniramine maleate (CTM) and phenylpropanolamine HCl (PPA) using three different system as described in the USP XXXVI/NF 31. The method depends on a separation onÂ  reversed-phase C8, C18 and Phenyl column for analysis PCT, GG, and CTM-PPA respectively with mobile phase water-methanol-acetic acid glacial (79:20:1) for PCT, water-methanol-acetic acid glacial (60:40:1,5) for GG and methanol-water (60:40) containing 0.34 g of monobasic potassium phosphate, 0.05 g of triethylamine hydrochloride, 0.25 g of sodium lauryl sulfate, and 0.1 mL of phosphoric acid in each 100 mL for CTM-PPA. Quantitation was achieved with UV detection at 280, 276 and 214 nm respectively for PCT, GG, and CTM-PPA based on peak area. The methods were validated in terms of system suitability test, specificity, precision, accuracy, linearity, and the results were found to be satisfactory.Â Keywords: RP-HPLC, Paracetamol, Guaiphenesin, Chlorpheniramine maleate, Phenylpropanolamine HCl.